2009
DOI: 10.1074/jbc.m806548200
|View full text |Cite
|
Sign up to set email alerts
|

The Frizzled-related sFRP2 Gene Is a Target of Thyroid Hormone Receptor α1 and Activates β-Catenin Signaling in Mouse Intestine

Abstract: The thyroid hormone receptor TR␣1 regulates intestinal development and homeostasis by controlling epithelial proliferation in the crypts. This involves positive control of the Wnt/␤-catenin pathway. To further investigate the effect of thyroid hormone-TR␣1 signaling on the intestinal epithelium proliferating compartment, we performed a comparative transcription profile analysis on laser microdissected crypt cells recovered from wild type animals with normal or perturbed hormonal status, as well as from TR knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 57 publications
11
83
1
Order By: Relevance
“…However, elucidation of the underlying mechanisms by which T 3 regulated requires further study. Previous reports have shown that TRs are potent inducer of tumorigenesis (Plateroti et al, 2006;Chen et al, 2008a;Kress et al, 2009). In this study, we report that the T 3 /TR controls the transcription of the CTSH gene and that T 3 -mediated cell migration appears to involve CTSH.…”
Section: Trb1mentioning
confidence: 49%
See 1 more Smart Citation
“…However, elucidation of the underlying mechanisms by which T 3 regulated requires further study. Previous reports have shown that TRs are potent inducer of tumorigenesis (Plateroti et al, 2006;Chen et al, 2008a;Kress et al, 2009). In this study, we report that the T 3 /TR controls the transcription of the CTSH gene and that T 3 -mediated cell migration appears to involve CTSH.…”
Section: Trb1mentioning
confidence: 49%
“…Thyroid hormone and TRa1 control epithelial cell proliferation and the expression of components of the Wnt pathway (Plateroti et al, 2006). The expression of the b-catenin and sFRP2 gene is regulated directly by TRa1, and the Wnt/ b-catenin signaling networks contribute to intestinal tumorigenesis (Kress et al, 2009). Chiloeches et al (2008) reported that ERK but not c-Jun N-terminal kinase or p38-MAPK is activated on exposure to T 3 in rat pituitary tumor (GH4C1) cells.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is very consistent with the diversified responses to THs among different organs during metamorphosis. It is worth noting that by comparing this study with the one by Kress et al (Kress et al, 2009), it is possible to reveal a consistent number of common target genes in the developing intestine of both Xenopus and mouse.…”
Section: Focus On Intestinal Epithelial Progenitorsmentioning
confidence: 92%
“…This function depends on the TR 1 receptor Plateroti et al, 2001;Flamant et al, 2002) and involves the transcriptional regulation of cell cycle control genes and of the Wnt/ -catenin pathway (Plateroti et al, 2006;Kress et al, 2009) (detailed in the next paragraph);…”
Section: Data From Engineered Micementioning
confidence: 99%
See 1 more Smart Citation